2015
DOI: 10.3855/jidc.6635
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, attitudes and practices of the Baka Pygmies of eastern Cameroon towards HIV and AIDS

Abstract: Introduction: The vulnerable health status of Pygmies is the result of their continual exposure to the modern world. The purpose of this study was to determine the prevalence of HIV and the attitudes and practices of Baka populations towards HIV infection. Methodology: A descriptive and cross-sectional study was conducted over a five-month period in 12 Pygmy camps. A questionnaire was completed to collect information, and anonymous screenings were held. For screening, whole blood was collected. The Determine H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For example, with condom use reported at less than 25% and HIV testing rates at less than 15%, the Pygmy population, a remote and small indigenous group dispersed throughout the Central African rainforests, may be at higher risk for HIV than other populations. 64,65 Economic development has been limited over the past three decades because of armed conflicts in different parts of the region. These conflicts have also affected health systems, which remain largely ineffective at responding to population needs.…”
Section: Central African Regionmentioning
confidence: 99%
“…For example, with condom use reported at less than 25% and HIV testing rates at less than 15%, the Pygmy population, a remote and small indigenous group dispersed throughout the Central African rainforests, may be at higher risk for HIV than other populations. 64,65 Economic development has been limited over the past three decades because of armed conflicts in different parts of the region. These conflicts have also affected health systems, which remain largely ineffective at responding to population needs.…”
Section: Central African Regionmentioning
confidence: 99%
“…Another study on KAP among secondary student in Cameroon by Essomba, reported that all respondents were aware of HIV/AIDS (Essomba et al, 2015). This outcome shows the effect of long civil war that affected South Sudan for more than three decades, on health system and other social services.…”
Section: Chapter ⅳ Resultsmentioning
confidence: 84%
“…In Cameroon, study shown that (75.7%) of participants reported having sex never used a condom during sex intercourse. But among those who used condom by gender, male used condom three time more than female (Essomba et al, 2015).…”
Section: Knowledge Attitudes and Practicesmentioning
confidence: 91%
See 2 more Smart Citations